2014
DOI: 10.1111/imm.12218
|View full text |Cite
|
Sign up to set email alerts
|

The up side of decidual natural killer cells: new developments in immunology of pregnancy

Abstract: SummaryEarly phases of human pregnancy are associated with the accumulation of a unique subset of natural killer (NK) cells in the maternal decidua. Decidual NK (dNK) cells that are devoid of cytotoxicity play a pivotal role in successful pregnancy. By secreting large amounts of cytokines/chemokines and angiogenic factors, dNK cells participate in all steps of placentation including trophoblast invasion into the maternal endometrium and vascular remodelling. In this review, we summarize some of dNK cell featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 97 publications
(129 reference statements)
1
105
0
2
Order By: Relevance
“…The first trimester of pregnancy is characterized by high numbers of dNK cells within the decidua, perhaps accounting for the low rate of congenital cytomegalovirus (CMV) infection (25). It has been shown that NK cells that infiltrate during the first trimester can switch their phenotype after sensing infection and that dNK cells can be found in the vicinity of infected cells within floating chorionic villi (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first trimester of pregnancy is characterized by high numbers of dNK cells within the decidua, perhaps accounting for the low rate of congenital cytomegalovirus (CMV) infection (25). It has been shown that NK cells that infiltrate during the first trimester can switch their phenotype after sensing infection and that dNK cells can be found in the vicinity of infected cells within floating chorionic villi (59).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to cross the placental barrier is one key determinant of invasive viruses and pathogens. Little is known about the ability of dNK cells to provide protective immunity against these agents (25). …”
Section: Introductionmentioning
confidence: 99%
“…Natural killer cells from decidual tissue in pregnant uterus (dNK) have unique phenotypical and functional properties compared to NK cells found in peripheral blood (pNK) (103). Mouse studies originally demonstrated that dNK cells function to support embryo implantation by secretion of numerous factors, including IFN-γ, to promote angiogenesis and trophoblast invasion (104).…”
Section: Splice Variants Of Ncrs Resulting In Distinct Receptor Isoformsmentioning
confidence: 99%
“…Decidual NK cells have been recognized as a distinct subtype with these cells comprising nearly 40 % of decidual cells in early pregnancy before decreasing to low levels by the last trimester (Sargent et al. ; Jabrane‐Ferrat and Siewiera ). They are distinct in that they show little cytolytic activity, are major secretors of angiogenic and trophoblast attracting cytokines such as VEGF, IL‐8, and IL‐10, and play an important role in promoting tolerance to cytotrophoblasts and directing their invasion of and subsequent remodeling of maternal vessels in the myometrium and endometrium (Hanna et al.…”
Section: Discussionmentioning
confidence: 99%